The biochemical content and antioxidant capacities of endemic tanacetum densum (Lab.) schultz bip. subsp. laxum, and tanacetum densum (lab.) schultz bip. subsp. amani heywood growing in turkey - Emre, İ. (Instituto Internacional de Ecologia, 2021)
Medicinal plants have a significant role in preventing and curing several diseases, and Tanacetum L. is one of these plants. The aim of the present study is to determine the fatty acid, lipid-soluble vitamin, sterol, phenolic content, and antioxidant capacity of Tanacetum densum subsp. laxum and Tanacetum densum subsp. amani, to compare the effect of altitude on the biochemical content and to compare systematically by using fatty acids and phenolics. This study showed that palmitic acid (C16:0) and stearic acid (C18:0) are major sources of saturated fatty acid and oleic acid (C18:1 n9), and linoleic acid (18:2 n6c) and a-linolenic acid (C18:3 n3) are the principal unsaturated fatty acids in the two endemic Tanacetum densum taxa. Also, this study found that the unsaturated fatty acid content (60.11±1.61%) of Tanacetum densum subsp. laxum was higher than the unsaturated fatty acid content (44.13±1.28%) of Tanacetum densum subsp. amani. And also, the ?6/?3 ratio of Tanacetum densum subsp. laxum (1.74) and Tanacetum densum subsp. amani (1.60) was found to be similar. However, this study determined that the lipid soluble vitamin and sterol content of two endemic Tanacetum taxa are low except for stigmasterol. Present study showed that catechin is principal phenolic in the Tanacetum densum taxa. This study also found that Tanacetum densum subsp. laxum and Tanacetum densum subsp. amani had the highest levels of catechin, vanillic acid, and caffeic acid content though the phenolic amounts, particularly catechin and quercetin, were dissimilar in the T. densum taxa. This study suggested that ecological conditions such as altitude may affect the biochemical content of two endemic Tanacetum densum taxa. Furthermore, the current study determined that two endemic Tanacetum L. taxa had potent radical scavenging capacities and found a correlation between total phenolics and antioxidant activity. © 2021, Instituto Internacional de Ecologia. All rights reserved.
O conteúdo bioquímico e as capacidades antioxidantes de tanacetum densum endêmico (Lab.) schultz bip. subsp. laxum e tanacetum densum (lab.) schultz bip. subsp. amani heywood que crescem na turquia
Keywords: Antioxidant capacity; Fatty acids; Lipid soluble vitamins; Sterols; Tanacetum densum